(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The global corporate landscape has undergone significant transformations, necessitating the adoption of various consolidation strategies to address challenges posed by evolving markets. With national and international markets deeply interconnected, companies are compelled to remodel their operations to remain competitive and align with organizational business objectives. In response to these challenges, companies have opted for inorganic growth through diverse consolidation strategies, such as mergers and acquisitions (M&A). The present paper explores the dynamic landscape of M&A as a pivotal catalyst for corporate growth and transformation. M&A activities have become integral strategies for companies seeking to expand market presence, enhance competitiveness, and achieve transformative objectives. The research delves into the relationship between M&A and leverage and examines the perceptions of pharmaceutical representatives and employees regarding relationship between M&A and leverage of firm. The study utilizes a mixed-method approach, combining quantitative and qualitative analyses. Primary data is gathered through a survey involving 200 pharmaceutical employees/representatives and experts from different departments with expertise in M&A processes, for assessing perceptions on relationship between M&A and leverage on firm growth. Secondary data from reports and other literature provides additional context for the research. The analysis encompasses key variables such as financial performance, market presence, and strategic outcomes associated with organizations employing strategic leverage through M&A. The findings contribute valuable insights into the strategic decision-making processes, challenges, and successes encountered by organizations leveraging mergers and acquisitions for growth. By examining the multifaceted aspects of strategic leverage, the present research seeks to provide a comprehensive understanding of how organizations navigate the complex landscape of M&A to achieve sustainable and transformative growth.